Lime mortars with rice husk ash for ancient masonry - Almeida, Nuno G. (2020)
This paper presents some preliminary results achieved in the aim of a research program with the main objective of evaluating the potential interest of using rice husk ashes on aerial lime based mortars for old buildings. The mechanical and physical characteristics and potential durability of lime mortars formulated with commercial rice husk ashes are analysed and their behaviour compared with a pure lime mortar. The results are also analysed taking into account the main aspects that are responsible for the compatibility between the new mortars and the original building materials. The potential durability of the tested mortars is evaluated through salt crystallization tests performed with sodium chloride and sodium sulphate solutions. The improvement of some properties of the lime mortars due to the presence of rice husk ashes pointed out the interest of the research in this domain, namely in what concerns the design of mortars with a moderately hydraulic behaviour for old buildings.